2010
DOI: 10.1016/j.jvs.2010.06.070
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy and safety of once-daily enoxaparin plus warfarin for the outpatient ambulatory treatment of lower-limb deep vein thrombosis in the TROMBOTEK trial

Abstract: Ambulatory treatment with enoxaparin plus warfarin seems to be effective in symptomatic healing and in clinical improvement by reducing thrombus formation and organization at all levels of lower extremity venous system with DVT, without a significant major bleeding risk. Therefore, the results of our conventional conservative treatment are in line with 1A level evidence reported in the recent American College of Chest Physicians guideline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Therefore, treatment strategies typically focus on prevention of long-term PTS. [11][12][13] As early thrombus removal appears to be critical in preventing PTS, particularly in young and active patients, the Society of Vascular Surgeons (SVS) and the American Venous Forum recommend using catheter-directed thrombectomy (CDT) with or without pharmaco-mechanical thrombolytic therapy (PMT) as first line treatment. Alternatively, open surgical venous thrombectomy (VT) has also been shown to decrease the risk of developing PTS, venous reflux, and venous obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, treatment strategies typically focus on prevention of long-term PTS. [11][12][13] As early thrombus removal appears to be critical in preventing PTS, particularly in young and active patients, the Society of Vascular Surgeons (SVS) and the American Venous Forum recommend using catheter-directed thrombectomy (CDT) with or without pharmaco-mechanical thrombolytic therapy (PMT) as first line treatment. Alternatively, open surgical venous thrombectomy (VT) has also been shown to decrease the risk of developing PTS, venous reflux, and venous obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…9 Data from TROMBOTEK trial among lower limb DVT patients in Turkey revealed long-term efficacy and safety of once-daily enoxaparin plus warfarin for the outpatient ambulatory treatment without a significant major bleeding risk. 20 However authors noted failure of warfarin in keeping INR within effective limits starting from the first three months of longterm follow-up. 20 In our analysis, TiTR was evaluated in patients followed up for at least three months.…”
Section: Discussionmentioning
confidence: 99%
“…20 However authors noted failure of warfarin in keeping INR within effective limits starting from the first three months of long-term follow-up. 20 In our analysis, TiTR was evaluated in patients followed up for at least three months. Thus achieved TiTR (34.3% of treatment period) in our cohort seems to be associated with the difficulty to reach therapeutic INR particularly in the initial treatment period, 9,21 not excluding the likelihood of future improvement in TiTR during continuation of VKA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with a widely-used anticoagulation guideline [8], intravenous unfractionated heparin loading and continuous infusion were performed to attain a therapeutic activated partial thromboplastin (aPTT) that was 1.5–2.5 times the control aPTT. We then converted intravenous anticoagulation to oral anticoagulant, warfarin (Kuparin; Hana Pharm Co., Ltd., Hwaseong, Korea), with a target international normalized ratio of 2.0–3.0 in all patients [911]. All patients took warfarin for at least 6 months.…”
Section: Methodsmentioning
confidence: 99%
“…We administered CDT to patients who had proximal lower extremity DVT, symptoms for ≤14 days, good functional status, life expectancy ≥2 years, and a low risk of bleeding. We started enoxaparin therapy (Clexane, Sanofi Winthrop Industrie SA; 1.0 mg/kg; Ambares, France), which is widely used as low-molecular-weight heparin, for all patients on the day of diagnosis with DVT, according to international guidelines [811].…”
Section: Methodsmentioning
confidence: 99%